A study of how tall buildings influence climatic factors and the need to create a different microclimate in a district - Serour Abdeslam (African Journal of Environmental Economics and Management, 2015)
The gradual change of climatic factors in a large agglomeration is primarily related to the expansion of urbanization. The construction of high-rise districts is currently in fashion worldwide, in part because high-rise buildings provide an image of prestige and prosperity for the country. However, the essential purpose of constructing high-rise buildings is to group together a large community in a restricted space. The aim of this study is to understand how tall buildings influence climatic factors and create a different microclimate in the district. This study is based on a 4-year series of measurements of the influence of the high-rise district of La Défense in Paris, France on climatic factors and air-pollution patterns. The results show that the construction of high-rise district creates a microclimate having higher temperatures than otherwise. Thus, high-rises tend to reinforce the phenomenon of urban heat islands. The construction of high-rises also has advantages as shown in this study, the upper-floor quarters benefit from natural air conditioning and a lower concentration of pollution. The construction and management of high-rise districts within cities is thus very important, and can generally lead to ecosystems with microclimates that are more favourable to urban dwellers.